Evidence for polymorphism of alloantigenic transplantation products of the histocompatibility locus (H-4) in linkage group I of Rattus norvegicus - Krsiaková, M; Kren, V; Jirásek, A (Folia biologica, 1981)
An alloantigenic transplantation system linked to the gene for albinism in linkage group I of Rattus norvegicus has been identified in the congenic pair LEW--LEW.C-4A and designated H-4. Alloantigenic transplantation products of the H-4 system are relatively "weak" because the majority of skin grafts exchanged between animals of the congenic pair (LEW--LEW.C-4A) survive permanently without previous sensitization of the recipients. Presensitization of the congenic recipients with lymphoid cells results in a marked increase in the incidence and acceleration of graft rejection. The testing of F1 hybrids of the eight inbred rat strains with strains LEW and LEW.C-4A by skin or tumour transplantation shows that alleles other than H-4a or H-41 are present in three strains, thereby demonstrating polymorphism of the H-4 system with the existence of minimally three alleles.
Keywords: krysa rodu Rattus; mužské pohlaví; genetická vazba; inbrední kmeny potkanů; Male; histokompatibilní antigeny; rejekce štěpu; experimentální nádory; Female; Lymphocytes; Alleles; transplantace nádorů; Neoplasm Transplantation; Graft Rejection; ženské pohlaví; Genetic Linkage; Rats; transplantace kůže; potkani inbrední LEW; Immunization; Transplantation Immunology; lymfocyty; Animals; imunizace; Histocompatibility Antigens; zvířata; Polymorphism, Genetic; transplantační imunologie; Skin Transplantation; polymorfismus genetický; Rats, Inbred Strains; Neoplasms, Experimental; alely; Rats, Inbred Lew